Kajian Pedagogis Guru Pendidikan Agama Kristen terhadap Motivasi Belajar Siswa di Era Pandemi Covid 19: Studi Kasus Siswa SMK Harapan Bagi Bangsa, Jakarta Utara - Pratiwi Eunike; Bobby Kurnia Putrawan (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2021)
In the era of the Covid-19 pandemic, distance or online learning is not an alternative, but the only option that must be done to prevent the increasing outbreak of Covid-19 through students and teachers. In conditions like this, there are many obstacles that must be faced both from the teacher as educators and students. From the teacher's side, pedagogical professionalism is demanded in carrying out their duties and responsibilities. From the aspect of students with reduced direct supervision from the teacher, causing low learning motivation. Teachers as education executors, specifically Religious Education teachers are required to be able to develop their pedagogical abilities to be able to overcome obstacles in online learning. The purpose of this study was to describe the pedagogical qualifications of Christian religious education teachers on student learning motivation in the Covid-19 pandemic era. The method used in this research is descriptive qualitative with data collection carried out by interviews and documentation as well as references to books related to research. The results of research on some outstanding students can increase learning motivation when Christian Religious Education teachers carry out their duties and responsibilities professionally by developing learning strategies and methods to increase student learning motivation in the Covid-19 pandemic era. Abstrak Di era pandemic Covid-19 pembelajaran jarak jauh atau daring bukan merupakan alternatif, melainkan satu-satunya pilihan yang harus dilakukan untuk men-cegah semakin meningkatnya wabah Covid-19 melalui siswa maupun guru. Dalam kondisi seperti ini banyak kendala yang harus dihadapi baik dari pihak guru sebagai pendidik maupun siswa. Dari pihak guru dituntut profesioanalitas pedagogis dalam menjalankan tugas dan tanggung jawabnya. Dari aspek siswa dengan berkurangnya pengawasan langsung dari guru sehingga menyebabkan moti-vasi belajar yang rendah. Guru sebagai eksekutor pendidikan, secara khusus guru Pendidikan Agama dituntut mampu mengembangkan kemampuan pedagogisnya untuk dapat mengatasi hambatan dalam pembelajaran online. Tujuan penelitian ini untuk mendeskripsikan kualifikasi pedagogis guru pendidikan agama Kristen terhadap motivasi belajar siswa di era pandemi Covid-19. Metode yang digunakan pada penelitian ini adalah kualitatif des-kriptif dengan pengumpulan data dilakukan dengan wawancara dan dokumentasi serta referensi buku-buku yang berkaitan dengan penelitian. Hasil penelitian pada beberapa siswa berprestasi dapat meningkat motivasi belajar ketika guru Pendidikan Agama Kristen menjalankan tugas dan tanggung jawab secara profesional dengan mengem-bangkan strategi dan metode pembelajaran untuk meningkatkan motivasi belajar siswa di era pandemi Covid-19.